1996
DOI: 10.1002/(sici)1096-9861(19961111)375:2<225::aid-cne4>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of integrin ?1 subunit in purkinje cells of rat and cerebellar mutant mice

Abstract: We found that integrin beta 1 subunit (INT beta 1)-immunoreactive Purkinje cells first appeared caudally at postnatal day (PD) 6 of rat and most Purkinje cells gradually became positive by PD 12. The expression of INT beta 1 was then suppressed in some of these cells, so that the positive Purkinje cells in the adult were organized into parasagittal bands interposed by negative cells throughout the vermis and hemispheres. When Purkinje cells were deprived of their climbing fiber innervation by inferior cerebell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Alternatively, or in combination, signal transduction events mediated by integrins might lead to altered cytoskeletal or membrane topology that strengthens the synapse. Along these lines, Murase and Hayashi have reported that expression of the integrin beta-1 subunit is increased by seizure activity, indicating that activity may alter synapses by altering integrin levels (124). Integrins can give rise to calcium influx (e.g.…”
Section: Synaptic Plasticity and Memory And Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, or in combination, signal transduction events mediated by integrins might lead to altered cytoskeletal or membrane topology that strengthens the synapse. Along these lines, Murase and Hayashi have reported that expression of the integrin beta-1 subunit is increased by seizure activity, indicating that activity may alter synapses by altering integrin levels (124). Integrins can give rise to calcium influx (e.g.…”
Section: Synaptic Plasticity and Memory And Learningmentioning
confidence: 99%
“…In the central nervous system, integrins of the beta-1 family appear to be widely expressed not only in developing neurons and glia, but also in the adult (45,124,125). A survey of integrin mRNA localization in adult brain by in situ hybridization detected mRNAs encoding alpha-1, alpha-3, alpha-4, alpha-5, alpha-6, alpha-7, alpha-8, alpha-v, beta-1, beta-4, and beta-5 in both neurons and glia in various brain regions (125).…”
Section: Cns Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Purkinje cells were expected to express INT␣1, because they express integrin ␤1 subunit (Murase and Hayashi, 1996), which is capable of forming a functional heterodimer with INT␣1, and also because they were found to be catecholaminergic neurons (Takada et al, 1993;Fujii et al, 1994;Sakai et al, 1995;Nelson et al, 1997) in addition to their GABAergic function (Ito and Yoshida, 1964;Obata and Takeda, 1969;Curtis et al, 1970;Fonnum et al, 1970;McLaughlin et al, 1974;Ito, 1984). We confirmed the TH-immunoreactivity of Purkinje cells in this study, but did not observe INT␣1 expression in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that integrin ␣v␤5 heterodimer is expressed in growing parallel fibers of postnatal cerebellum (Murase and Hayashi, submitted), and also that a subset of adult Purkinje cells express integrin ␤1 subunit (Murase and Hayashi, 1996). These findings encouraged us to examine the expression of various types of integrins in the central nervous system.…”
mentioning
confidence: 90%